2014
DOI: 10.1007/s00360-014-0877-1
|View full text |Cite
|
Sign up to set email alerts
|

The evolution of nitric oxide signalling in vertebrate blood vessels

Abstract: Nitric oxide is one of the most important signalling molecules involved in the regulation of physiological function. It first came to prominence when it was discovered that the vascular endothelium of mammals synthesises and releases nitric oxide (NO) to mediate a potent vasodilation. Subsequently, it was shown that NO is synthesised in the endothelium by a specific isoform of nitric oxide synthase (NOS) called NOS3. Following this discovery, it was assumed that an endothelial NO/NOS3 system would be present i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
42
0
4

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(50 citation statements)
references
References 155 publications
4
42
0
4
Order By: Relevance
“…Indeed, a recent phylogenetic analysis of the evolution of NOS genes in metazoans revealed that teleost fish have a nNOS form (referred to as NOS1/3) and an iNOS gene (Gonzalez‐Domenech and Munoz‐Chapuli, ; Andreakis et al., ). However, most recently Donald and colleagues (), using Bayesian phylogenetic analysis and a web‐based protein analysis tool, demonstrated that there are three NOS genes in garfish, L. oculatus . Unlike nNOS gene, which shows a high degree of conservation during vertebrates’ evolution, L. oculatus eNOS gene shows little shared synteny and it remains to be determined whether this is a functionally expressed gene (syntenic block).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, a recent phylogenetic analysis of the evolution of NOS genes in metazoans revealed that teleost fish have a nNOS form (referred to as NOS1/3) and an iNOS gene (Gonzalez‐Domenech and Munoz‐Chapuli, ; Andreakis et al., ). However, most recently Donald and colleagues (), using Bayesian phylogenetic analysis and a web‐based protein analysis tool, demonstrated that there are three NOS genes in garfish, L. oculatus . Unlike nNOS gene, which shows a high degree of conservation during vertebrates’ evolution, L. oculatus eNOS gene shows little shared synteny and it remains to be determined whether this is a functionally expressed gene (syntenic block).…”
Section: Discussionmentioning
confidence: 99%
“…This is of relevance as, even if nos3 sequence has not been identified in dipnoi, lungfishes possess many tetrapod‐like gene sets (for references, see ref. ) which may account for the nos3 presence in these fish. In all piscine species, the enzyme localizes at the EE which lines the ventricular trabeculae and, to a lesser extent, in both atrial and ventricular myocardiocytes, and at the level of the visceral pericardium.…”
Section: Nos Cardiac Expression and Localizationmentioning
confidence: 94%
“…At the same time, in fish, a nNOS isoform, that includes an endothelial‐like consensus, may cover some functional behaviours typical of the eNOS isoform identity . The discovery of a putative nos3 gene in actinopterygian recently suggested that the nos1 gene must have duplicated early in gnathostome evolution, before the actinopterygian‐sarcopterygian split, but after the appearance of the chondrichthyan fish lineage . Despite the above data, studies mainly performed by our research group, using physio‐pharmacological approaches, as well as NADPH‐diaphorase and immunostaining with heterologous mammalian anti‐eNOS antibodies, show the presence of an “eNOS‐like” activity in the heart of several teleost species .…”
Section: Nos Cardiac Expression and Localizationmentioning
confidence: 96%
See 1 more Smart Citation
“…Immediately after birth a significant induction of NOS3 rapidly provides a strong stimulus of pulmonary vasodilation, initiating, and maintaining pulmonary perfusion that enhances oxygen uptake. The phylogenetic evolution of NOS has been extensively defined by several groups (1820). The evolutionary process is complex, involving at least two episodes each of genomic duplication and gene duplication.…”
Section: From the Apgar Score To Vertebrate Evolutionmentioning
confidence: 99%